THE INFLUENCE OF DIFFERENT STRATEGIES ON THE PRODUCTION OF OIL FIELDS STIMULATED BY WATERFLOODING - Martini, R. F.; A. Cavalcante Filho, J. S.; Schiozer, D. J. (Revista de Engenharia Térmica, 2006)
Quality map is an important tool which can assist in the definition and refinement of production strategies, since it indicates the production potential of each place of the reservoir, combining several parameters that influence oil recovery efficiency. This work has used numerical simulation to analyse the performance of different production strategies used in waterflood projects for an offshore reservoir; these strategies included peripheral injection/central production, a 5-spot injection/production scheme and a strategy defined with the assistance of a quality map; after the initial process of strategy definition, all schemes were optimised. The refinement procedure was assisted by an expert system, which proposes well modifications based on the analysis of economic and technical parameters and stores the analysed parameters in a databank. The results show that the use of the quality map improved to a great extent the processes of strategy definition and refinement, yielding better results and requiring fewer simulation runs. The application of quality maps to petroleum reservoirs is still quite recent, with very few works published; however, they present great potential for the E&P industry, as presented here.